Exosomal non-coding RNAs (ncRNAs) as potential biomarkers in tumor early diagnosis - Chang, Jingyue; Zhang, Lingquan; Li, Zeting; Qian, Chungen; Du, Juan (Biochimica et biophysica acta. Reviews on cancer, 2024)
Exosomes, extracellular vesicles carrying a cargo rich in various non-coding RNAs (ncRNAs), have emerged as crucial mediators of intercellular communication. Their stability, abundance, and specificity make exosomal ncRNAs promising candidates for biomarker discovery. The discovery of exosomal ncRNAs has unveiled a novel avenue for the exploration of biomarkers in tumor early diagnosis. This review consolidates current knowledge on the role of exosomal ncRNAs as potential biomarkers in the early detection of various tumors. We provide an overview of recent studies demonstrating the diagnostic potential of exosomal ncRNAs across multiple cancer types, highlighting their sensitivity, specificity, and feasibility for early detection. This review underscores the potential of exosomal ncRNAs as non-invasive biomarkers for early tumor diagnosis, paving the way for improved clinical outcomes through timely intervention and personalized management strategies.